The Integration of Key Risks and Performance Indicators Using COSO-2017 in Medium Enterprise Fintech - Prasetyo, Aries Heru (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2025)
Key performance indicator is the ultimate goal pursued by financial technology companies. In most cases, the achievement of the goal has become major concern for top management. They need firmly mechanism to signal any possible risk that might interfere the process. At this context, the role of key risk indicator become very important. Unfortunately, focus in this issue is still rare and inconclusive. This research tries to propose conceptual framework to integrate key risk indicator into key performance indicators. Using COSO-2017 as the basic theory, we found that one alternative way is by combining both qualitative and quantitative risk analysis to detrude the key performance indicator in a quarterly basis. Series of medium enterprise financial technology company’s past performance must be treated using proper statistical tools while setting the most ideal targets for each quarter, thus rebalancing the optimism from the top management. Henceforth, the availability of historical loss event data would be useful to measure probability of risk occurrence and its possible impact objectively. We provide a conceptual framework to deal with this issue, followed by assessment for selected performance indicator in medium enterprise fintech. The study enclosed with conclusion and direction for further agenda.